(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The Indian diaspora, comprising over 32 million individuals across the globe, serves as a significant instrument of India’s soft power. This paper explores how the diaspora promotes India’s cultural, economic, and diplomatic influence through activities such as cultural festivals, economic remittances, and advocacy in host countries.